Baby-sitters' island adventure - Martin, Ann M., 1955- (New York : Scholastic, 1990)
Claudia and Dawn and four other kids sail out to Greenpoint Island. But a storm blows up and the kids never return from the island.
4.2
3-6
Keywords: Shipwrecks -- Fiction; Shipwrecks -- Fiction